2021
DOI: 10.1155/2021/7073878
|View full text |Cite
|
Sign up to set email alerts
|

Could Executive Compensation Incentive Enhance the Efficiency of Enterprise Resource Allocation? An Empirical Study from China

Abstract: Corporate executives have the decision-making power of resource allocation, and efficient resource allocation is an important measure of high-quality development of enterprises. It is a focal issue whether the compensation incentive can promote the executives to make better use of the enterprise resource allocation. We investigate this question using the data of the Chinese listed companies in 2015–2019 based on Data Envelopment Analysis (DEA) and fixed effect model. The results show the following: (1) both mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Regarding economic outcomes: Many scholars posit that stock incentives can notably curtail inefficient corporate investments, thereby enhancing investment efficiency (Tang et al, 2021). They are also believed to foster green innovation and ultimately bolster corporate performance (Yin et al, 2021). Qiao et al (2023), utilizing a multiple linear regression model on samples of equity incentive plans rolled out in China from 2010 to 2018, noted that the operational performance of companies post-implementation of these equity incentive plans exhibited a polarized trend.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding economic outcomes: Many scholars posit that stock incentives can notably curtail inefficient corporate investments, thereby enhancing investment efficiency (Tang et al, 2021). They are also believed to foster green innovation and ultimately bolster corporate performance (Yin et al, 2021). Qiao et al (2023), utilizing a multiple linear regression model on samples of equity incentive plans rolled out in China from 2010 to 2018, noted that the operational performance of companies post-implementation of these equity incentive plans exhibited a polarized trend.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding economic outcomes: Many scholars posit that stock incentives can notably curtail inefficient corporate investments, thereby enhancing investment efficiency (Tang et al ., 2021). They are also believed to foster green innovation (Wu et al ., 2022) and ultimately bolster corporate performance (Yin et al ., 2021). Qiao et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Z. Li et al, 2020) are all affected by the equity incentive mechanism. Based on short-term incentives, scholars have also concluded that compensation incentives are of great significance to optimizing the strategic choice of enterprises, resource allocation (X. N. Yin et al, 2021), and improving production performance (Banerjee & Homroy, 2018).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Li et al, 2020) are all affected by the equity incentive mechanism. Based on short-term incentives, scholars have also concluded that compensation incentives are of great significance to optimizing the strategic choice of enterprises, resource allocation (X. N. Yin et al, 2021), and improving production performance (Banerjee & Homroy, 2018). The strong sensitivity of compensation performance of senior management teams can inhibit the conditions required for earnings manipulation and enhance the quality of earnings (Kim et al, 2022).…”
Section: Executive Incentives and Enterprise Innovationmentioning
confidence: 99%
“…Fan et al (2017) measured the inter-provincial capital allocation efficiency through the marginal capital-output ratio and concluded that there was a nonlinear relationship between international technological spillovers and capital allocation efficiencies [43]. Yin et al (2021) regarded that executive compensation played an inverted U-shaped role in resource allocation efficiencies of enterprises [44]. Cheng, et al (2020) employed the residual of the regression, the difference between actual investment and expected investment to measure the efficiency of enterprise capital allocation, and considered that the compensation incentive of management at different life cycle stages has different effects [45].…”
Section: Enterprise Capital Allocation Efficiencymentioning
confidence: 99%